2016
DOI: 10.1080/10942912.2016.1210161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyphenols fromCaralluma fimbriataon acrylamide formation and lipid oxidation—An integrated approach of nutritional quality and degradation of fried food

Abstract: The objective of this study was to investigate the utilization of Caralluma fimbriata an edible succulent cactus as natural antioxidants for retarding acrylamide formation, lipid oxidation, and the degradation of bioactive compounds in French fries due to frying at 190°C. The fresh Caralluma fimbriata extract exhibited the highest phenolic content of 96.4 ± 0.1 mg gallic acid equivalent/g when the raw potato extract showed significantly 27.4 ± 0.3 mg GAE/g before frying. The Caralluma fimbriata extract had the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Deep-fat frying employing high temperatures can change the structure polyphenols, vitamins, and antioxidants in potato snacks (Nems et al, 2015). Babu et al (2017) observed a 10% degradation of total phenolic content (TPC) in French fries treated with Caralluma fimbriata extract before frying at 190°C. The catechin content decreased by 18% after frying and all other bioactive compounds (flavanols, quercitin, ascorbic acid, and so on) showed a reduction of no higher than 20% after frying.…”
Section: Introductionmentioning
confidence: 99%
“…Deep-fat frying employing high temperatures can change the structure polyphenols, vitamins, and antioxidants in potato snacks (Nems et al, 2015). Babu et al (2017) observed a 10% degradation of total phenolic content (TPC) in French fries treated with Caralluma fimbriata extract before frying at 190°C. The catechin content decreased by 18% after frying and all other bioactive compounds (flavanols, quercitin, ascorbic acid, and so on) showed a reduction of no higher than 20% after frying.…”
Section: Introductionmentioning
confidence: 99%
“…found the antioxidants in green tea reduced the acrylamide content in fried potatoes. Babu et al . found polyphenols from Caralluma fimbriata could inhibit the formation of acrylamide and the oxidation of lipids.…”
Section: Resultsmentioning
confidence: 99%
“…There are several hypotheses on Maillard reaction formation pathways . Lipid oxidation is a secondary pathway for the formation of acrylamide in which acrylic acid, a direct precursor of acrylamide, can be formed by lipids oxidative degradation of acrolein . Currently processed potato snack products are the main source of acrylamide in the diet…”
Section: Introductionmentioning
confidence: 99%
“…The use of CFE as a therapeutic intervention is well known in Ayurvedic medicine [ 32 ]. CFE can also be used as a natural antioxidant [ 33 ]. Other therapeutic applications of CFE reported in the literature include carminative, febrifugal, anthelmintic, antirheumatic, anti-inflammatory, antinociceptive, and antioxidant actions [ 25 ].…”
Section: C Fimbriata: An Edible Wild Medicinal Plantmentioning
confidence: 99%